Development of a web-based learning platform for informatics using an inquiry approach to enhance learning outcomes in high school - Siregar, Nova Desima Handayani; Sugiharto, Sugiharto; Dalimunthe , Amirhud (ARKA INSTITUTE, 2025)
This study aims to develop an Informatics learning website based on Inquiry Learning to improve student learning outcomes at SMA Free Methodist. The background of this research lies in the low level of student engagement in Informatics classes and the limited availability of digital media that supports exploration and independent critical thinking. Inquiry Learning is considered an appropriate approach for fostering active, discovery-based learning, while the website serves as an accessible and interactive platform for delivering instructional content. The study used the Research and Development (R&D) method, applying the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects included 30 tenth-grade students. Data collection tools comprised expert validation sheets, student response questionnaires, observations, and learning outcome tests. The results indicate that the developed website is valid according to evaluations from content and media experts. Students responded very positively to the interactive features such as quizzes, tutorial videos, discussion forums, and inquiry-based assignments. The inquiry learning model applied through the website effectively enhanced students' conceptual understanding, critical thinking skills, and overall academic performance. In conclusion, the Inquiry Learning-based Informatics website is highly effective and suitable for use as an innovative digital learning medium at the senior high school level.